Design and Performance Evaluation of a Cementitious Repair Grouting Mortar for Cement Pavement Slab Cavity - Sibo Huang; Chong Li; Zejie Zhang (Buildings)
To address the severe damage caused by voids beneath cement concrete pavement slabs, which compromise pavement performance and lifespan, there is an urgent need to develop an economical and efficient grouting material for slab void repair. This study employed a two-step orthogonal experiment design (OED) method to optimize the composition of grouting material. Results show that the plain cement mortar achieves the best flowability, setting time, compressive strength, or flexural strength when the water-to-binder ratio is 0.375, with 20% quartz sand, 2% coal ash, and 5% ground calcium carbonate. For the high-performance cement mortar developed, the optimal water-to-binder ratio is 0.35, with 0.5% redispersible latex powder, 0.2% polypropylene fiber, 0.6% water-reducing agent, 0.8% early-strength agent, and 2.0% expansion agent. Under these optimal conditions, the grouting material with a flowability of 15 s has a compressive strength and flexural strength of 76.98 MPa and 11.89 MPa, respectively, and achieves 77.4% of its 28-day compressive strength and 94.0% of its 28-day flexural strength by day 3. This grouting material also possesses a slight expansion within 0.1% at 3, 7, and 28 days, categorizing it as a micro-expansion mortar. The bond strength at the mortar-concrete interface exceeds the tensile strength of the mortar itself, ensuring no debonding at the interface before grouting material failure. The XRD, SEM, and infrared spectra results explain the early strength development mechanism of this cement mortar.